Respon Konstruktif terhadap Kritik Negatif: Studi Kasus Strategi Komunikasi Dakwah pada Kanal YouTube Jeda Nulis - Nia Darmawati; Dinda Luthfiaturrahmah Alhaq; Canra Krisna Jaya (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The development of digital da'wah requires preachers not only to understand religious material but also to possess strong public communication and reputation management skills. The Jeda Nulis channel, managed by Habib Husein Ja'far Al-Hadar, has become a popular da'wah channel in Indonesia, actively engaging in dialogue with the digital public. However, this channel also receives various forms of negative criticism that can impact the image of da'wah in the digital space. This study aims to analyze the forms of negative criticism that appear on the Jeda Nulis channel, their impact on the channel's public image, and the da'wah communication strategies used to respond constructively to criticism. The study used descriptive qualitative methods using comment content analysis, video content observation, and secondary literature interviews. The results show that negative criticism is not always detrimental but can instead become a space for productive dialogue if handled with appropriate communication strategies: comment moderation, open clarification, a humanistic approach, and consistency of da'wah messages. This strategy successfully maintained and even strengthened the image of the Jeda Nulis channel as an inclusive, open, and moderate da'wah medium.